MAKNA RITUAL LODONG ME SUKU RAWA DALAM HUBUNGAN DENGAN SAKRAMEN PEMBAPTISAN DI PAROKI SANTA PERAWAN MARIA RATU TANARAWA - Maria Menti; Petrus Tamelab; Antonius I.N Tukan (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
The understanding and appreciation of the Lodong Me ritual in relation to the sacrament of baptism by the Rawa tribe in the Parish of the Virgin Mary Queen of Tanarawa remains minimal. This is because the congregation tends to consider the Lodong Me ritual more important. Consequently, most congregation members prioritize the Lodong Me ritual over the Sacrament of Baptism. This study aims to explore the deeper meaning of the Lodong Me ritual in relation to the Sacrament of Baptism. The method used is a qualitative method with a phenomenological approach through interviews and documentation with traditional elders, parish priests, religious teachers, and congregation members. The collected data is processed and presented phenomenologically. The results indicate that the congregation's understanding of the meaning of the Lodong Me ritual and the Sacrament of Baptism remains very limited. This can be improved through catechesis and faith-building activities, which are expected to enhance the congregation's understanding of the Sacrament of Baptism.